Depoimento dos surdos sobre as atitudes que facilitaram e que dificultaram suas relações sociais durante a adolescência - Chagas, Paula Adriana Cunha (2007)
This research had as its purpose an investigation of the attitudes that facilitated and hindered the social relations of the deaf people during their adolescence and, looking for analyzed the deposition of these individuals. The theoretical foundation follows authors who considers deafness a difference, no a deficiency, and authors who characterize the adolescence from the point of view in the focus of evolutive psychology. The research was qualitative, using and adopted a questioner with open questions as instrument to collection of the data. The analysis provided evidenced that family participation contributed for the development of these deaf individuals, even when not making use of sign language to communicate with them and when ignoring the importance of the sign language for the development of a deaf person. Verbal communication, however, was cited as one of the biggest difficulties faced by these individual, as much in the home environment, as in school environment, as well as in the other places they frequent. The difficulty of establishing friendship bonds with non deaf adolescent was also noted. In spite of all subjects knowing and using brazilian sign language in some communities, all the subjects of this research emphasized that they could communicate orally in other communities showing the possibilities of enrichment of their lives by various means of communication.